Pengaruh Waktu Pemasakan dan Konsentrasi NaOH Terhadap Penurunan Kadar Lignin Pulp dari Batang Pisang Kepok dengan Proses Soda - Maulana, Imam; Widayatno, Tri (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Banana is a plant that has very high cellulose content so it can be used as a raw material for making pulp. This research was conducted with the aim of knowing the effect of cooking time and sodium hydroxide concentration on reducing the lignin content of banana stem pulp by soda process. The cooking solution used in the soda process is NaOH solution. With various concentrations of NaOH 20%, 25%, and 30% and cooking time 40, 80, and 120 minutes. The highest lignin content was 1.8785% during pulping for 40 minutes with 20% NaOH concentration. While the lowest lignin content was 1.3093% during pulping for 120 minutes with 30% NaOH concentration.